The Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area - Yanti Budiyantini; Sheilla Alviany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Urban growth is referred to as the expansion of an urban area into the surrounding environment. The expansion gives rise to sub-urban development phenomena called peri-urbanization, which occurs in physical, economic, and social changes. This paper identifies the socio-economic transformations in the peri-urban Bandung Metropolitan Area, based on the theoretical determination of socio-economic variables and peri-urban typology. The study emphasizes the main feature of the socio-economic changes in each peri-urban typology based on the discriminant analysis. Socio-economic transformation is analyzed on the variables of population density, household economic sectors, people's education, and the number of prosperous families. A Peri-urban area is divided into three typologies: Predominantly Urban (dominantly urban characteristics), Semi-Urban, and Potential Urban Area (dominantly rural characteristics). The data and information required for the study are generated mainly from secondary sources. The study shows that socio-economic transformation occurs in each peri-urban typology at different levels of change. The different characteristics of peri-urban typology and its proximity to the city center result in a high socio-economic transformation rate.